High-crack-resistance wear-resistant cement as well as preparation method and application thereof
By using high-active blends and composite early strength agents in sulfaaluminate cement, the crack resistance and wear resistance of cement are improved, and the problems of insufficient performance and high preparation cost of sulfaaluminate cement are solved, and new design and development direction.
Patent Information
- Application Number
- CN202411543690.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The crack resistance and wear resistance of sulfur aluminate cement are poor, and the preparation cost is high, and the compatibility of each component is poor, which limits its application in building cementitious materials.
High crack resistance is prepared by ball milling and heat treatment by using components such as high-active blends (high titanium slag, waste ceramic powder and fly ash) and composite early strength agents (triethanolamine, calcium bromide and anhydrous sodium sulfate). Grind cement to improve the compactness, mechanical strength and crack resistance of cement.
It realizes high crack and wear resistance of cement materials, reduces preparation costs, and improves the compatibility of various components, providing new ideas for the design and development of sulfur aluminate cement.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a high-crack-resistant and wear-resistant cement and a preparation method and application thereof. Background Art
[0002] Sulphoaluminate cement is usually made by mixing gypsum, bauxite and limestone in a certain proportion and calcining at low temperature. It is a hydraulic cementitious material with excellent properties of rapid hardening, early strength, low alkalinity, frost resistance, impermeability and corrosion resistance. The main minerals of its clinker are C2S and C4A3$. Sulphoaluminate cement has the characteristics of rapid solidification and hardening. During large-scale pouring, the temperature at the center of the pouring body may rise sharply, which may easily lead to excessive concentration of hydration heat, and then cause cracks due to excessive temperature difference between the inside and outside. In addition, the wear resistance of sulphoaluminate cement is relatively poor. When used in some parts that need to withstand wear, it may be necessary to add additional aggregates or take other reinforcement measures to improve its wear resistance.
[0003] In the prior art, in order to improve the crack resistance and wear resistance of sulphoaluminate cement, fiber materials or additives (retarders, expansion agents or wear-resistant agents) are often added to increase the toughness and strength of sulphoaluminate cement. However, the selection of fiber materials and the compatibility of additives have become new problems restricting the development of sulphoaluminate cement, and are likely to increase the preparation cost of sulphoaluminate cement and reduce the economic value of sulphoaluminate cement.
[0004] Based on this, the research and development of a sulphoaluminate cement with excellent crack resistance and wear resistance is of great significance to the development of building cementitious materials. Summary of the invention
[0005] Aiming at the problems that the crack resistance and wear resistance of sulphoaluminate cement in the prior art are poor, the preparation cost is high, and the compatibility of the components is poor, the present invention provides a high crack resistance and wear resistance cement and its preparation method and application. The present invention uses sulphoaluminate cement clinker, high-activity admixture, composite early strength agent, water reducer and air entraining agent as raw materials to successfully prepare a sulphoaluminate cement with high crack resistance and wear resistance, effectively solving the above problems existing in the current sulphoaluminate cement, and providing a new idea for the design and development of sulphoaluminate cement.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The first aspect of the present invention provides a highly crack-resistant and wear-resistant cement, comprising the following raw material components by mass: 80-120 parts of sulphoaluminate cement clinker, 40-60 parts of high-activity admixture, 10-15 parts of composite early strength agent, 5-10 parts of water reducer and 1-3 parts of air entraining agent; Wherein, the composite early strength agent comprises triethanolamine, calcium bromide and anhydrous sodium sulfate; The high-activity admixture is a mixture of high-titanium slag, waste ceramic powder and fly ash.
[0007] Compared with the prior art, the present invention adds highly active admixtures to cement materials, and utilizes high-titanium slag, waste ceramic powder and fly ash to compound the three, which greatly improves the density of sulphoaluminate cement. Among them, high-titanium slag plays a micro-aggregate filling effect, makes up for the tiny pores in cement, and enhances the density of cement. In addition, high-titanium slag can play the role of microcrystalline nucleus in the late stage of cement hydration, accelerate the nucleation growth of sulphoaluminate cement clinker minerals, and thus improve the mechanical strength and wear resistance of cement materials. The active silica and alumina in the waste ceramic powder are easy to undergo secondary hydration reaction with calcium hydroxide, and the generated CSH gel further improves the density of cement, and the gel can wrap the micro-aggregate of high-titanium slag, so that it has a more excellent filling effect. The addition of fly ash can effectively alleviate the development of cement cracks, increase the peak value of the hydration heat release rate of cement materials, and also form an induced activation effect with high-titanium slag. The two complement each other, induce each other to increase the hydration rate, and promote the formation of their own hydration products, thereby improving the crack resistance and mechanical properties of cement.
[0008] The addition of composite early strength agent can not only accelerate the hydration of mineral components in sulphoaluminate cement clinker, but also utilize the emulsifying effect of triethanolamine to decompose the surface colloidal film produced by cement hydration, strengthen the compactness of the solid phase volume structure of cement, and achieve the purpose of ensuring the early and late strength of cement at the same time. Among them, calcium bromide can promote the early hydration reaction of cement by increasing the calcium ion concentration, and improve the early strength by increasing the early compactness of the cement microstructure. The addition of anhydrous sodium sulfate can enhance the ion concentration of cement liquid phase, play a compression role in expanding the double electron layer, promote the decomposition of tricalcium silicate in clinker to accelerate the hydration reaction, and then react with calcium ions to promote the formation of calcium aluminate and monosulfur hydrated calcium sulphoaluminate, thereby achieving the effect of early strength and fast hardening and avoiding cracks.
[0009] In summary, the high crack-resistant and wear-resistant cement provided by the present invention has good mechanical properties, excellent wear resistance and crack resistance, and utilizes the synergistic effect of various raw material components to successfully solve the problems of poor crack resistance and wear resistance of sulphoaluminate cement in the prior art, high preparation cost, and poor compatibility of various components, providing new ideas for the design and development of sulphoaluminate cement.
[0010] Preferably, the mass ratio of triethanolamine, calcium bromide and anhydrous sodium sulfate is 1:50:50-2:50:50.
[0011] Preferably, the specific surface area of the high titanium slag is 300m 2 / kg-400m 2 / kg.
[0012] Preferably, the high-activity admixture includes the following raw material components by mass: 30%-40% high-titanium slag, 20%-30% waste ceramic powder and the balance fly ash.
[0013] The high-titanium slag is a granular or block-shaped waste slag obtained by quenching or naturally cooling the slag discharged during the process of smelting pig iron using vanadium-titanium ore as raw materials.
[0014] The high-titanium slag includes the following chemical components in percentage by mass: 30%-35% CaO, 20-25% SiO2, 10%-15% TiO2 and 20-35% Al2O3.
[0015] Further preferably, the preparation method of the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it to obtain a mixture; S2. The mixed material is heat treated at 80-120° C., and then ball-milled for a second time to obtain a high-activity admixture.
[0016] More preferably, in S1, the rotation speed of the ball milling treatment is 300 rpm-500 rpm, and the time of the ball milling treatment is 40 min-60 min.
[0017] More preferably, in S2, the heat treatment holding time is 2h-5h.
[0018] More preferably, in S2, the rotation speed of the secondary ball milling is 800 rpm-1200 rpm, and the time of the secondary ball milling is 25 min-35 min.
[0019] Preferably, the mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 40%-50%; C4A3$: 10%-25%; C4AF: 5%-15%; CaSO4: 10%-15% and the remainder of other components.
[0020] Further preferably, the other components include any one or more of SiO2, f-CaO, Al2O3 or Fe2O3.
[0021] Preferably, the particle size of the high-activity admixture is 100 μm-200 μm.
[0022] Preferably, the water reducer is any one of a polycarboxylic acid type water reducer or a naphthalene type high efficiency water reducer.
[0023] Preferably, the air entraining agent is alkylbenzene sulfonate.
[0024] The second aspect of the present invention provides a method for preparing the highly crack-resistant and wear-resistant cement, comprising the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2: uniformly mix the early strength agent, water reducing agent and air entraining agent, and uniformly mix with the high-activity admixture to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0025] The third aspect of the present invention provides the use of the highly crack-resistant and wear-resistant cement or the highly crack-resistant and wear-resistant cement prepared by the preparation method of the highly crack-resistant and wear-resistant cement in the field of construction.
[0026] In summary, the present invention uses sulphoaluminate cement clinker, high-activity admixture, composite early strength agent, water reducer and air entraining agent as raw materials to successfully prepare a sulphoaluminate cement with high crack resistance and wear resistance. By utilizing the synergistic effect of each component raw material, it has been tested that the cement material provided by the present invention has a crack resistance performance that can reach LV level, and the 28d wear loss is only 1.2kg / m 2 The technical solution of the present invention successfully solves the problems of poor crack resistance and wear resistance of sulphoaluminate cement, high preparation cost and poor compatibility of various components, and provides a new idea for the design and development of sulphoaluminate cement. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The high-titanium slag used in the following examples and comparative examples includes the following chemical components in percentage by weight: 32.8% CaO, 24.6% SiO2, 11.7% TiO2 and 30.9% Al2O3; the specific surface area of the high-titanium slag is 350m 2 / kg.
[0029] Example 1 This embodiment provides a highly crack-resistant and wear-resistant cement, which specifically includes the following contents: The highly crack-resistant and wear-resistant cement comprises the following raw material components by mass: 100 parts of sulphoaluminate cement clinker, 50 parts of high-activity admixture, 12 parts of composite early strength agent, 8 parts of polycarboxylate water reducer and 2 parts of alkylbenzene sulfonate; Wherein, the composite early strength agent is triethanolamine, calcium bromide and anhydrous sodium sulfate in a mass ratio of 1.5:50:50; The high-activity admixture comprises the following raw material components: 35% high-titanium slag, 25% waste ceramic powder and 40% fly ash; The preparation method of the highly crack-resistant and wear-resistant cement comprises the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2: uniformly mix the composite early strength agent, water reducing agent and air entraining agent, and uniformly mix with the high-activity admixture to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0030] The method for preparing the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it at a speed of 400 rpm for 50 min to obtain a mixture; S2. The mixture is heat treated at 100° C. for 4 hours, and then ball-milled for a second time at a rotation speed of 1000 rpm for 30 minutes to obtain a high-activity admixture with a particle size of 150 μm.
[0031] The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 47.2%; C4A3$: 22.6%; C4AF: 12.3%; CaSO4: 11.7%, 3.2% SiO2 and 3% f-CaO.
[0032] Example 2 This embodiment provides a highly crack-resistant and wear-resistant cement, which specifically includes the following contents: The highly crack-resistant and wear-resistant cement comprises the following raw material components: 120 parts of sulphoaluminate cement clinker, 42 parts of high-activity admixture, 10 parts of composite early strength agent, 10 parts of polycarboxylate water reducer and 3 parts of alkylbenzene sulfonate; Wherein, the composite early strength agent is triethanolamine, calcium bromide and anhydrous sodium sulfate in a mass ratio of 2:50:50; The high-activity admixture comprises the following raw material components by mass: 40% high-titanium slag, 20% waste ceramic powder and 40% fly ash; The preparation method of the highly crack-resistant and wear-resistant cement comprises the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2: uniformly mix the composite early strength agent, water reducing agent and air entraining agent, and uniformly mix with the high-activity admixture to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0033] The method for preparing the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it at a speed of 500 rpm for 40 min to obtain a mixture; S2. The mixture is heat treated at 120° C. for 5 hours, and then ball-milled for a second time at a rotation speed of 1200 rpm for 25 minutes to obtain a high-activity admixture with a particle size of 100 μm.
[0034] The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 41.9%; C4A3$: 24.8%; C4AF: 10.1%; CaSO4: 14.7%, 5.3% SiO2 and 3.2% f-CaO.
[0035] Example 3 This embodiment provides a highly crack-resistant and wear-resistant cement, which specifically includes the following contents: The highly crack-resistant and wear-resistant cement comprises the following raw material components: 80 parts of sulphoaluminate cement clinker, 60 parts of high-activity admixture, 15 parts of composite early strength agent, 10 parts of polycarboxylate water reducer and 1 part of alkylbenzene sulfonate; Wherein, the composite early strength agent is triethanolamine, calcium bromide and anhydrous sodium sulfate in a mass ratio of 1:50:50; The high-activity admixture comprises the following raw material components by mass: 30% high-titanium slag, 30% waste ceramic powder and 40% fly ash; The preparation method of the highly crack-resistant and wear-resistant cement comprises the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2: uniformly mix the composite early strength agent, water reducing agent and air entraining agent, and uniformly mix with the high-activity admixture to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0036] The method for preparing the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it at a speed of 450 rpm for 60 min to obtain a mixture; S2. The mixture is heat treated at 100° C. for 4 hours, and then ball-milled for a second time at a rotation speed of 1000 rpm for 30 minutes to obtain a high-activity admixture with a particle size of 120 μm.
[0037] The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 42.3%; C4A3$: 22.6%; C4AF: 12.7%; CaSO4: 14.3%, 3.2% f-CaO and 4.9% Al2O3.
[0038] Example 4 This embodiment provides a highly crack-resistant and wear-resistant cement, which specifically includes the following contents: The highly crack-resistant and wear-resistant cement comprises the following raw material components by mass: 100 parts of sulphoaluminate cement clinker, 50 parts of high-activity admixture, 12 parts of composite early strength agent, 8 parts of polycarboxylate water reducer and 2 parts of alkylbenzene sulfonate; Wherein, the composite early strength agent is triethanolamine, calcium bromide and anhydrous sodium sulfate in a mass ratio of 1.5:50:50; The high-activity admixture comprises the following raw material components by mass: 35% high-titanium slag, 25% waste ceramic powder and 40% fly ash; The preparation method of the highly crack-resistant and wear-resistant cement comprises the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2: uniformly mix the composite early strength agent, water reducing agent and air entraining agent, and uniformly mix with the high-activity admixture to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0039] The method for preparing the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it at a speed of 400 rpm for 50 min to obtain a mixture; S2. The mixture is heat treated at 100° C. for 4 hours, and then ball-milled for a second time at a rotation speed of 1000 rpm for 30 minutes to obtain a high-activity admixture with a particle size of 150 μm.
[0040] The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 47.2%; C4A3$: 23.6%; C4AF: 9.3%; CaSO4: 12.7%, 3.2% SiO2 and 4% f-CaO.
[0041] Example 5 This embodiment provides a highly crack-resistant and wear-resistant cement, which is different from Embodiment 1 in that the alkylbenzene sulfonate is replaced with an equal amount of rosin resin, and specifically includes the following contents: The highly crack-resistant and wear-resistant cement comprises the following raw material components: 100 parts of sulphoaluminate cement clinker, 50 parts of high-activity admixture, 12 parts of composite early strength agent, 8 parts of polycarboxylic acid type water reducer and 2 parts of rosin resin; Wherein, the composite early strength agent is triethanolamine, calcium bromide and anhydrous sodium sulfate in a mass ratio of 1.5:50:50; The high-activity admixture comprises the following raw material components: 35% high-titanium slag, 25% waste ceramic powder and 40% fly ash; The preparation method of the highly crack-resistant and wear-resistant cement comprises the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2: uniformly mix the composite early strength agent, polycarboxylic acid type water reducing agent and rosin resin, and uniformly mix with the high-activity admixture to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0042] The method for preparing the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it at a speed of 400 rpm for 50 min to obtain a mixture; S2. The mixture is heat treated at 100° C. for 4 hours, and then ball-milled for a second time at a rotation speed of 1000 rpm for 30 minutes to obtain a high-activity admixture with a particle size of 150 μm.
[0043] The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 47.2%; C4A3$: 22.6%; C4AF: 12.3%; CaSO4: 11.7%, 3.2% SiO2 and 3% f-CaO.
[0044] Comparative Example 1 This comparative example provides a high crack resistance and wear resistance cement, which is different from Example 1 in that the composite early strength agent is replaced by an equal amount of calcium formate, specifically including the following contents: The highly crack-resistant and wear-resistant cement comprises the following raw material components by mass: 100 parts of sulphoaluminate cement clinker, 50 parts of high-activity admixture, 12 parts of calcium formate, 8 parts of polycarboxylate water reducer and 2 parts of alkylbenzene sulfonate; The high-activity admixture comprises the following raw material components: 35% high-titanium slag, 25% waste ceramic powder and 40% fly ash; The preparation method of the highly crack-resistant and wear-resistant cement comprises the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2: Evenly mix the calcium formate, water reducing agent and air entraining agent, and evenly mix with the high-activity admixture to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0045] The method for preparing the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it at a speed of 400 rpm for 50 min to obtain a mixture; S2. The mixture is heat treated at 100° C. for 4 hours, and then ball-milled for a second time at a rotation speed of 1000 rpm for 30 minutes to obtain a high-activity admixture with a particle size of 150 μm.
[0046] The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 47.2%; C4A3$: 22.6%; C4AF: 12.3%; CaSO4: 11.7%, 3.2% SiO2 and 3% f-CaO.
[0047] Comparative Example 2 This comparative example provides a high crack resistance and wear resistance cement, which is different from Example 1 in that the high activity admixture is replaced with an equal amount of high titanium slag, specifically including the following contents: The highly crack-resistant and wear-resistant cement comprises the following raw material components by mass: 100 parts of sulphoaluminate cement clinker, 50 parts of high-titanium slag, 12 parts of composite early strength agent, 8 parts of polycarboxylate water reducer and 2 parts of alkylbenzene sulfonate; Wherein, the composite early strength agent is triethanolamine, calcium bromide and anhydrous sodium sulfate in a mass ratio of 1.5:50:50; The preparation method of the highly crack-resistant and wear-resistant cement comprises the following steps: Step 1: Weigh the raw materials of each component according to the designed ratio and set aside; Step 2, mixing the calcium formate, water reducing agent and air entraining agent evenly, and mixing with high-titanium slag evenly to obtain a first cement mixture; Step 3: Add sulphoaluminate cement clinker into the first cement mixture and perform homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
[0048] The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 47.2%; C4A3$: 22.6%; C4AF: 12.3%; CaSO4: 11.7%, 3.2% SiO2 and 3% f-CaO.
[0049] In order to further reflect the technical effect of the present invention, the present invention conducted relevant performance tests on the cement materials obtained in Examples 1-5 and Comparative Examples 1-2, specifically including the following contents: Crack resistance (crack resistance grade): Reference standard JGJ / T193-2009, grade classification LI (total crack area per unit area ≥ 1000mm 2 / m 2 )、L-II(1000mm 2 / m 2 >Total cracking area per unit area ≥700mm 2 / m 2 )、L-III(700mm 2 / m 2 >Total cracking area per unit area ≥400mm 2 / m 2 )、L-IV(400mm 2 / m 2 >Total cracking area per unit area ≥100mm 2 / m 2 ), LV (total cracking area per unit area <100mm 2 / m 2 ), the higher the grade, the better the crack resistance.
[0050] Wear resistance test The wear resistance test of the cement materials obtained in Examples 1-5 and Comparative Examples 1-2 was carried out on the cement materials with a wear capacity of 28 days with reference to the national standard JC / T42-2005 "Test method for wear resistance of cement mortar".
[0051] Table 1 Performance test results of cement materials obtained from Examples 1-5 and Comparative Examples 1-2
[0052] It can be seen from Table 1 that the cement material obtained in the embodiment of the present invention has excellent crack resistance and wear resistance. In particular, the cement material obtained in Example 1 has a crack resistance that can reach LV level, and the 28d wear loss is only 1.2 kg / m 2 .
[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly crack-resistant and wear-resistant cement, characterized in that: The raw material components include: 80-120 parts of sulphoaluminate cement clinker, 40-60 parts of high-activity admixture, 10-15 parts of composite early strength agent, 5-10 parts of water reducing agent and 1-3 parts of air entraining agent; Wherein, the composite early strength agent comprises triethanolamine, calcium bromide and anhydrous sodium sulfate; The high-activity admixture is a mixture of high-titanium slag, waste ceramic powder and fly ash.
2. The highly crack-resistant and wear-resistant cement according to claim 1, characterized in that: The mass ratio of triethanolamine, calcium bromide and anhydrous sodium sulfate is 1:50:50-2:50:50; and / or The specific surface area of the high titanium slag is 300m 2 / kg-400m 2 / kg.
3. The highly crack-resistant and wear-resistant cement according to claim 1, characterized in that: The high-activity admixture comprises the following raw material components by mass: 30%-40% of high-titanium slag, 20%-30% of waste ceramic powder and the balance of fly ash.
4. The highly crack-resistant and wear-resistant cement according to claim 3, characterized in that: The preparation method of the high-activity admixture comprises the following steps: S1. Weigh each raw material component according to the designed ratio, and ball-mill it to obtain a mixture; S2. The mixed material is heat treated at 80° C.-120° C. and ball-milled for a second time to obtain a high-activity admixture.
5. The highly crack-resistant and wear-resistant cement according to claim 4, characterized in that: In S1, the rotation speed of the ball milling treatment is 300 rpm-500 rpm, and the time of the ball milling treatment is 40 min-60 min; and / or In S2, the heat treatment holding time is 2h-5h; and / or In S2, the rotation speed of the secondary ball milling is 800 rpm-1200 rpm, and the time of the secondary ball milling is 25 min-35 min.
6. The highly crack-resistant and wear-resistant cement according to claim 1, characterized in that: The mineral composition of the sulphoaluminate cement clinker includes the following components in percentage by mass: C2S: 40%-50%; C4A3$: 10%-25%; C4AF: 5%-15%; CaSO4: 10%-15% and the remainder of other components.
7. The highly crack-resistant and wear-resistant cement according to claim 1, characterized in that: The particle size of the high-activity admixture is 100 μm-200 μm; and / or The water reducer is any one of a polycarboxylic acid type water reducer or a naphthalene type high efficiency water reducer; and / or The air entraining agent is alkylbenzene sulfonate.
8. The method for preparing the highly crack-resistant and wear-resistant cement according to any one of claims 1 to 7, characterized in that: The steps include: Step 1, weighing the raw materials of each component according to the designed proportion, and uniformly mixing the composite early strength agent, water reducing agent, air entraining agent and high-activity admixture to obtain a first cement mixture; Step 2: adding the sulphoaluminate cement clinker into the first cement mixture and performing homogenization treatment to obtain highly crack-resistant and wear-resistant cement.
9. Use of the highly crack-resistant and wear-resistant cement as described in any one of claims 1 to 7 or the highly crack-resistant and wear-resistant cement prepared by the preparation method of the highly crack-resistant and wear-resistant cement as described in claim 8 in the field of developing new building materials.
Citation Information
Patent Citations
Production method of marine engineering cement block
CN105198337A
Method for producing high-salinity maritime work cement through mineral waste residue waste materials
CN105271854A
Rapid curing and co-doping system grouting material for subway engineering and preparation method of rapid curing and co-doping system grouting material
CN114262198A
Maritime work cement, preparation method thereof, concrete and application thereof
CN114349372A
Early strength agent for improving strength and durability of concrete and preparation method thereof
CN116354643A